Disruptive life event or reflexive instrument? On the regulation of hospital mergers from a quality of care perspective. Issue 4 (5th May 2020) - de Kam, David; van Bochove, Marianne; Bal, Roland
Abstract : Purpose: Despite the continuation of hospital mergers in many western countries, it is uncertain if and how hospital mergers impact the quality of care. This poses challenges for the regulation of mergers. The purpose of this paper is to understand: how regulators and hospitals frame the impact of merging on the quality and safety of care and how hospital mergers might be regulated, given their uncertain impact on quality and safety of care. Design/methodology/approach: This paper studies the regulation of hospital mergers in The Netherlands. In a qualitative study design, it draws on 30 semi-structured interviews with inspectors from the Dutch Health and Youth Care Inspectorate (Inspectorate) and respondents from three hospitals that merged between 2013 and 2015. This paper draws from literature on process-based regulation to understand how regulators can monitor hospital mergers. Findings: This paper finds that inspectors and hospital respondents frame the process of merging as potentially disruptive to daily care practices. While inspectors emphasise the dangers of merging, hospital respondents report how merging stimulated them to reflect on their care practices and how it afforded learning between hospitals. Although the Inspectorate considers mergers a risk to quality of care, their regulatory practices are hesitant. Originality/value: This qualitative study sheds light on how merging might affect key hospital processes and daily care practices. It offers opportunities for the regulation of hospital mergers that acknowledges rather than aims to dispel the uncertain and potentially ambiguous impact of mergers on quality and safety of care.